The Impact of Financial Technology on the Profitability of Chinese Commercial Banks - Xue, Yuan (Universiti Malaysia Sarawak, 2025)
In recent years, the inexorable trend of deep integration between finance and technology has been propelled by the emergence of cutting-edge technologies such as big data and artificial intelligence, alongside the rapid advancement of internet finance. The ascendancy of FinTech has disrupted the established position and advantages traditionally held by commercial banks within the industry. Recognizing that their conventional business models are no longer viable in today’s fiercely competitive environment, banks have come to realize the urgent need for digital transformation. Against this backdrop, they have astutely seized opportunities presented by FinTech and made substantial investments in developing FinTech technologies to transcend traditional business paradigms and achieve transformative upgrades. However, profitability stands as a pivotal determinant for survival and growth of commercial banks, hence it is imperative to explore how FinTech applications impact their profitability. In light of the current state of FinTech development in China and the profitability situation of commercial banks, this study adopts theoretical framework based on the long tail theory, financial innovation, technological spillover, and financial disintermediation. It selects data from 50 listed commercial banks between 2012 and 2023 as samples and constructs a panel data model. Based on the Digital Inclusive Finance Index developed by Peking University and using the distribution of bank branches in each province as weights, a FinTech index is constructed as the core independent variable. Factor analysis is employed to synthesize a comprehensive profitability indicator from three dimensions: security, liquidity and profitability, serving as the dependent variable. Control variables are selected at both the macroeconomic and bank-specific levels, and a fixed effects model is utilized to empirically examine the non-linear impact of FinTech on the profitability of banks. Additionally, an income diversification moderating variable is introduced to explore its mediating role in the relationship between FinTech and bank profitability. The impact of FinTech on the profitability of commercial banks is primarily examined through the channels of competition and risk. Based on the theoretical and empirical findings, it is demonstrated that there exists a U-shaped non-linear relationship between FinTech development and bank profitability, with a threshold value of 2.86. The negative effects observed in the early stages of FinTech development are primarily attributed to heightened competition and risks. Commercial banks can mitigate these adverse effects during this developmental phase by enhancing the diversification of their revenue structures. As the adoption of FinTech progresses, its impact on bank profitability shifts from negative to positive. In addition, the grouping regression analysis indicates that regional banks are more significantly influenced by FinTech compared national banks. Furthermore, in contrast to the pre-pandemic period, the impact of FinTech on the profitability of commercial banks has become increasingly pronounced since the outbreak of the pandemic. Based on these analytical findings, this thesis proposes the following countermeasures: The government should implement supportive policies for FinTech, increase investment in FinTech infrastructure construction, and refine the regulatory framework for FinTech innovation. Moreover, commercial banks must integrate FinTech into their long-term strategic planning and prioritize boosting their innovation capabilities. They should also adjust their revenue structures to effectively mitigate the challenges posed by FinTech. Additionally, commercial banks should deepen collaboration with FinTech firms, enhance risk management and early warning systems, and pursue a differentiated development strategy. Finally, they should expedite the development of digital infrastructure to ensure robust support for FinTech applications.